Caracterización de aguas residuales generadas en instalaciones militares –estudio de caso Ejercito Nacional de Colombia (2017)
Considering the wide and diverse field of space action of the Colombian National Army, the need to characterize its waste water generated in such a way that the resulting information can be used in the future to guide the design and management of the new and existing infrastructure associated with this type of liquid wastes. Under this understanding, the present study represents a contribution towards the knowledge of the dynamic nature of the wastewater generated in the Military Installations. The quantitative analysis of the tributary wastewater flows to various WWTPs of the Colombian National Army was carried out by means of the present study. Likewise, the average characterization of these flows was established, also calculating their daily pollutant loads and per capita loads. Finally, the treatment requirements of these liquid wastes were identified in the framework of the current discharges standard in the country (Res. MADS 631/2015), while three possible configurations of WWTP for the treatment of these waters were proposed.